A seismic refraction and wide-angle reflection exploration in 2002 on the Mizuho Plateau, East Antarctica-Outline of observations (JARE-43)- - Hiroki Miyamachi; Shigeru Toda; Takeshi Matsushima; Masamitsu Takada; Yasuhiro Takahashi; Daisuke Kamiya; Atsushi Watanabe; Mikiya Yamashita; Morio Yanagisawa (Antarctic Record, 2003)
A seismic refraction and wide-angle reflection exploration was successfully conducted along a profile crossing the JARE-41 seismic profile on the Mizuho Plateau, in East Antarctica, in the austral summer season of 2001-2002 (JARE-43). One hundred sixty-one seismic stations were temporarily installed along a profile about 151 km long and seven large shots with about 700 kg of dynamite were fired. In addition, one shot with charge size of 20 kg was also arranged along the profile. The obtained seismic records show the clear onsets of the first arrivals at distances of less than 100 km from each large shot. In particular, seismic waves traveling through the ice sheet and dispersed surface waves were clearly observed. Some later reflection phases were also detected. The obtained first travel time data show that the ice sheet is a two-layered structure consisting of an upper layer with a P wave velocity of 2.7-2.9 km/s and a lower layer of 3.7-3.9 km/s. The thickness of the upper layer is estimated to be about 36-45 m. The apparent velocity in the basement rock just beneath the ice sheet is 6.1-6.2 km/s in the central and southern parts of the profile and almost 5.9 km/s in the northern part. This report describes basic outlines of the exploration and the obtained seismic data.